Process algebra : equational theories of communicating processes - Baeten, J. C. M. (Cambridge tracts in theoretical computer science, 2010)
"Process algebra is a widely accepted and much used technique in the specification and verification of parallel and distributed software systems. This book sets the standard for the field. It assembles the relevant results of most process algebras currently in use, and presents them in a unified framework and notation." "The authors describe the theory underlying the development, realization, and maintenance of software that occurs in parallel or distributed systems. A system can be specified in the syntax provided, and the axioms can be used to verify that a composed system has the required external behavior. As examples, two protocols are completely specified and verified in the text: the Alternating-Bit communication Protocol, and Fischer's Protocol of mutual exclusion." "The book serves as a reference text for researchers and graduate students in computer science, offering a complete overview of the field and referring to further literature where appropriate."--Jacket